UGT1A1 Genetic Variations and a Haplotype Associated with Neonatal Hyperbilirubinemia in Indonesian Population. (23rd January 2018) - Wisnumurti, Dewi A.; Sribudiani, Yunia; Porsch, Robert M.; Maskoen, Ani M.; Abdulhamied, Lola I.; Rahayuningsih, Sri E.; Asni, Eni K.; Sleutels, Frank; Kockx, Christel E. M.; van Ijcken, Wilfred F. J.; Sukadi, Abdurachman; Achmad, Tri H.
Abstract : Neonatal hyperbilirubinemia (NH) is a common finding in newborn babies in Indonesia. Common and rare variants of UGT1A1 have been known to contribute to NH etiology. This study aims to identify UGT1A1 genetic variation and haplotype associated with NH in Indonesian population. DNA was isolated from 116 cases and 115 controls and a targeted-deep sequencing approach was performed on the promoter, UTRs, and exonic regions of UGT1A1 . Determining association of common variants and haplotype analysis were performed using PLINK and Haploview. Ten and 4 rare variants were identified in cases and controls, respectively. The UGT1A1 rare variants frequency in cases (5.17%) was higher than that in controls (1.7%). Four of those rare variants in cases (p.Ala61Thr, p.His300Arg, p.Lys407Asn, and p.Tyr514Asn) and three in controls (p.Tyr79X, p.Ala346Val, and p.Thr412Ser) are novel variants. The frequencies of p.Gly71Arg, p.Pro229Gln, and TA7 common variants were not significantly different between cases and controls. A haplotype, consisting of 3 major alleles of 3′ UTRs common variants (rs8330C>G, rs10929303C>T, and rs1042640C>G), was associated with NH incidence (p = 0.025 ) in this population. Using targeted-deep sequencing and haplotype analysis, we identified novel UGT1A1 rare variants and disease-associated haplotype in NH in Indonesian population.